Artificially induced drought stress affects seasonal foliar litterfall, nutrient contents, and nutrient masses in mature European beech (Fagus sylvatica [L.]) and Norway spruce (Picea abies [L.] Karst.) - Matthias Ulbricht; Peter Biber; Thomas Rötzer; Enno Uhl; Karin Pritsch; Bernhard Michalke; Hans Pretzsch (Trees, Forests and People)
We examined the effects of drought-induced stress on foliar litter production, nutrient contents, and nutrient masses in mature European beech (Fagus sylvatica [L.]) and Norway spruce (Picea abies [L.] Karst.) over a two-year period (October 2015–September 2017) in southern Bavaria. A rainfall exclusion experiment was conducted with six control plots receiving normal rainfall and six roof plots excluding rainfall. Abscised leaf and needle biomass, as well as the contents and masses of calcium (Ca), potassium (K), magnesium (Mg), nitrogen (N), and phosphorus (P), were monitored across two non-vegetation periods (October–February: NV1, NV2) and two vegetation periods (March–September: V1, V2).Foliar litter on control plots (set at 100 %) was 4000, 329, 4501, 403 kg/ha for European beech and 3534, 1146, 1352, 607 kg/ha for Norway spruce across the four observation periods (NV1, V1, NV2, V2). Roof plots yielded 2917 (73 %), 364 (111 %), 3710 (82 %), 358 (89 %) kg/ha for European beech and 5841 (165 %), 1040 (91 %), 899 (67 %), 447 (74 %) kg/ha for Norway spruce. Significant differences between control and roof plots were observed only during NV1.Foliar K contents were significantly lower under drought in both species. For European beech, values were 2.83, 3.83, 2.76, 4.37 g/kg (control plots), compared to 2.38 (84 %), 3.08 (80 %), 2.30 (83 %), 4.01 (92 %) g/kg (roof plots). For Norway spruce, values were 2.64, 2.77, 2.51, 2.13 g/kg (control plots), compared to 2.26 (86 %), 2.33 (84 %), 2.01 (80 %), 1.66 (78 %) g/kg (roof plots). Drought also significantly decreased foliar Ca content in Norway spruce during NV2, from 8.61 to 7.04 g/kg (82 %).Foliar nutrient masses aligned more closely with biomass abscission patterns than with nutrient translocation patterns. European beech predominantly exhibited significantly reduced abscised nutrient masses under drought during NV1 and NV2, while Norway spruce initially showed significantly increased abscised nutrient masses in NV1, followed by a marked decline in subsequent seasons.We concluded that European beech responded to drought stress by reducing foliage biomass production, suggesting a potential acclimation strategy, whereas Norway spruce mitigated water loss through transpiration by shedding its needles. However, Norway spruce failed to compensate for the initial high needle losses by regenerating sufficient new needles, indicating its lower resilience to drought.